101k views
3 votes
-2(8x-1)=5(1-3x)

What is the answer to this equation?

User Cordero
by
4.7k points

1 Answer

2 votes

Answer:

x= -3

Explanation:

−2(8x−1)=5(1−3x)

Step 1: Simplify both sides of the equation.

−2(8x−1)=5(1−3x)

(−2)(8x)+(−2)(−1)=(5)(1)+(5)(−3x)(Distribute)

−16x+2=5+−15x

−16x+2=−15x+5

Step 2: Add 15x to both sides.

−16x+2+15x=−15x+5+15x

−x+2=5

Step 3: Subtract 2 from both sides.

−x+2−2=5−2

−x=3

Step 4: Divide both sides by -1.

−x

−1

=

3

−1

x=−3

User Ivan Sieder
by
5.2k points